Execução cível sob a perspectiva do acesso à justiça pela via dos direitos: princípios da atividade executiva em um contexto de descentralização da jurisdição - Henrique Rabelo Quirino (2023)
Jurisdiction is traditionally understood as a State power; more precisely, the power of the judiciary to resolve disputes between citizens, applying the law. However, with the development of more comprehensive notions of access to justice, the very concept of jurisdiction has changed, with authors defending the existence of jurisdictional activity outside of the State itself. The present work revisits the concept of jurisdiction, in order to understand how the more contemporary concept harmonizes with the idea of ​​access to justice through rights, the theoretical framework of the research. From this, the dissertation intends to examine the proposal to dejudiciarize civil execution. The analysis, which encompasses a both theoretical and practical bias, seeks to determine whether the dejudicialization of the executive procedure would imply changes in the principles that govern execution, and, if so, in what way; and how this procedure should be designed to guarantee the expansion of access-to-justice. In this sense, the work reinforces the need for reflection and care in the development and implementation of justice administration policies. Despite the continuous need to improve judicial institutions, this cannot lead to a reduction in access to effective rights, both in individual and collective terms, whether directly or covertly.